(untitled) (Issues in Social and Environmental Accounting (ISEA), 2025)
This study examines the influence of behavioural control mechanisms, specifically organisational culture and reward systems, on green performance within Environmentally Sensitive Industries (ESIs). Grounded in Simons’ Levers of Control framework, the research adopts a quantitative approach to explore how these behavioural controls contribute to sustainability outcomes. Data were collected through survey questionnaires from 142 respondents and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results demonstrate that both organizational culture and reward systems significantly enhance green performance, underscoring complementary roles in fostering environmental responsibility. These findings offer valuable insights for managers seeking to strengthen sustainability practices by strategically aligning behavioural control systems with environmental objectives. The study further emphasizes the strategic role of management accounting in supporting sustainability-driven decision-making, highlighting how an integrated approach to cultural values and performance-based rewards can drive superior environmental outcomes. By advancing understanding of behavioral controls in ESIs, this research contributes to the broader discourse on management control systems (MCS) and sustainability, offering practical implications for organisations aiming to achieve competitive advantage through responsible environmental performance.